Perancangan Forum Diskusi Mobile Online Learning - Agus Putranto (Bina Nusantara University, 2012)
The utilization of e-learning can improve effectiveness and flexibility of learning. One important activities e-learning feature is a discussion forum. Communication between educators and students in class will be more effective if combined with communication through a discussion forum. Binus Online Learning is selected as a place of research. Binus Online Learning is a program of Bina Nusantara University that offers online study activities, which most of the students are invited to have self study activities. The aim of this research is to do requirement analysis and then to design a forum discussion called M-learning for Binus Online Learning so that it will be beneficial for the students that they can easily use the faster access. In this research, used are data collection through surveis, and analysis based on are literature study and the current systems, while rich picture and user interface are used for design. The results obtained are some features for the mobile learning discussion forum.